A Tribute to Margaret Grace Stineman, MD. (July 2021) - Houtrow, Amy
Abstract: The field of physical medicine and rehabilitation mourns the death of Margaret Grace Stineman, MD. She was an incredibly productive researcher who helped to shape the delivery of rehabilitation care. She was a trusted colleague, mentor, and friend to many. Her outstanding accomplishments were acknowledged by her numerous awards and her election into honorary societies. Dr Stineman spent her career at the University of Pennsylvania and retired as Professor Emeritus in 2014. She is survived by her mother and innumerable colleagues and friends who were touched by her passion, intelligence, and dedication.